NUEVOS HALLAZGOS SOBRE LA PENSATRIZ SALMANTINA (1777): AUTORÍA, ORIGINALIDAD Y TEXTO DE LA IDEA SEGUNDA. - PASTOR COLOMER, BLANCA (Dieciocho: Hispanic Enlightenment)
This article brings to light new discoveries concerning the eighteenthcentury newspaper La Pensatriz Salmantina, published in Salamanca in 1777, of which only the first issue was previously known. It fits in the category of critical press and is the second known example of journalism published by women in eighteenth-century Spain (the first being La Pensadora Gaditana [1763], which it attempts to emulate). Herein are resolved some previously unknown issues that surrounded the Salamancan newspaper since its initial publication, adding details related to its debated authorship or the originality of its approach. In addition, the second number is published here in its entirety.